Developing and validating a student-perceived market orientation scale in higher education / Voon Boo Ho, Nagarajah Lee & Firdaus Abdullah - Ho, Voon Boo; Lee, Nagarajah; Abdullah, Firdaus (2006)
Empirical research findings worldwide have shown that market orientation has its strategic importance for organizational excellence and competitiveness. Undoubtedly, developing a market-oriented organization for competitive success, though not easy, is deemed necessary. Besides, the voices of customer need to be taken into consideration to avoid market offering mismatch. Market orientation is crucial for the institutions of higher learning so as to produce graduates who are learned, competent and marketable.